1996
DOI: 10.1182/blood.v87.6.2244.bloodjournal8762244
|View full text |Cite
|
Sign up to set email alerts
|

The use of 7-amino actinomycin D in identifying apoptosis: simplicity of use and broad spectrum of application compared with other techniques

Abstract: The detection and quantitation of apoptotic cells is becoming increasingly important in the investigation of the role of apoptosis in cellular proliferation and differentiation. The pathogenesis of hematologic disorders such as aplastic anemia and the development of neoplasia are believed to involve dysregulation of apoptosis. To quantitate accurately the proportion of apoptosis cells within different cell types of a heterogeneous cell population such as blood or bone marrow, a method is required that combines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
134
0
6

Year Published

1997
1997
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 297 publications
(142 citation statements)
references
References 31 publications
2
134
0
6
Order By: Relevance
“…[12][13][14][15] There are many ways to detect apoptosis: detection of typical morphologic features of the cell population by light or electron microscopy, time-lapse photography, detection of DNA fragmentation by gel electrophoresis, the TUNEL assay, and flow cytometry-based methods (for example, PI staining). In this study, flow cytometric analysis with 7AAD was used 7,8) to determine the extent of drug-induced apoptosis on tumor cell lines. 7AAD stains live, apoptotic, and dead cells differentially because of the altered accessibility of DNA in each subpopulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14][15] There are many ways to detect apoptosis: detection of typical morphologic features of the cell population by light or electron microscopy, time-lapse photography, detection of DNA fragmentation by gel electrophoresis, the TUNEL assay, and flow cytometry-based methods (for example, PI staining). In this study, flow cytometric analysis with 7AAD was used 7,8) to determine the extent of drug-induced apoptosis on tumor cell lines. 7AAD stains live, apoptotic, and dead cells differentially because of the altered accessibility of DNA in each subpopulation.…”
Section: Discussionmentioning
confidence: 99%
“…Survival was expressed as the percentage of viable cells in treated samples relative to nontreated control cells. Analysis of apoptosis by flow cytometry with 7-aminoactinomycin D (7AAD) staining This assay was developed according to the method previously described by Schmid et al 7) and validated by Philpott et al 8) Briefly, 7AAD (Sigma Chemical Company) was dissolved in acetone and diluted in PBS to a concentration of 200 µg/ml. This solution was kept at −20°C and protected from light until use.…”
Section: Cell Linesmentioning
confidence: 99%
“…Moreover, the anti-apoptotic Representative experiment of the effects of ATRA (1 lmol/l) on the apoptosis of marrow CD34 + cells deprived of haematopoietic growth factors. CD34 + cells selected on d 0 were cultured in a serum-free medium for 7 d and the apoptotic status of the CD34 + cells was determined by the analysis of membrane permeability to high doses of 7AAD (Philpott et al, 1996). Effects of ATRA (1 lmol/l) on the apoptosis of marrow CD34 + cells deprived of haematopoietic growth factors.…”
Section: Discussionmentioning
confidence: 99%
“…High concentrations of ATG (equivalent to serum levels found during infusion) inhibited colony growth from CD34 cells. This was con®rmed using 7 amino-actinomycin D (7AAD) staining (Schmid et al, 1994a,b;Philpott et al, 1996), which showed that high ATG concentrations caused the death of normal CD34 cells.…”
mentioning
confidence: 98%